Katian (Upper Ordovician) carbon isotope chemostratigraphy in the Neixiang area, central China; implications for intercontinental correlation - Jing Xiuchun, Jing Xiuchun; Stouge, Svend; Tian Yufeng, Tian Yufeng; Wang Xunlian, Wang Xunlian; Zhou Hongrui, Zhou Hongrui (Geological magazine, 2019)
The Katian (Upper Ordovician) Shiyanhe Formation at the Sigang section, Neixiang area, Henan Province, central China, has been investigated for carbon isotope (δ13Ccarb) chemostratigraphy. The carbon isotopic data document signal between the two major Ordovician positive shifts in δ13C, the early Katian Guttenberg and the Hirnantian excursions. The Kope (Ka1/2), Fairview (Ka2/3), Waynesville (Ka3/4), Whitewater (Ka4) excursions and a doubtful Elkhorn (Ka4) excursion are identified herein. The continuous and well-defined conodont zonal succession of the Sigang section provides a secure biostratigraphic framework for the mid-late Katian carbon isotope chemostratigraphy in China. Correlation between carbon-isotope data curve and the relative sea-level changes shows no clear correspondence, and hence the sea-level change is probably not the main driver of δ13C excursions during the Katian. Intercontinentally, the mid-late Katian carbon isotope excursions, identified mainly in the North American and Baltoscandian successions, are useful for improving long-distance stratigraphic correlations. This further suggests that these excursions represent global perturbations in the carbon cycle.